Design and synthesis of novel 1,2,3,4-tetrazines as new anti-leukemia cancer agents - Eyilcim, Oznur; Gunay, Fulya; Gunkara, Omer Tahir; Ng, Yuk Yin; Ulucan, Ozlem; Erden, Ihsan (WILEY, 2023)
A series of novel 1,2,3,4-tetrazines were designed and synthesized. 1H-NMR spectroscopy, 13C NMR spectroscopy, and HRMS were used to determine the structures of this novel compounds. Computational approaches suggested that DHFR is a putative target for the newly synthesized 11 compounds. Extensive molecular dynamics simulations followed by molecular docking simulations were employed to evaluate DHFR as a potential target protein. The anticancer activities of the compounds were evaluated against five different types of leukemia cell lines (Jurkat, Nalm-6, Reh, K562, and Molt-4) and one non-leukemic cell line (Hek293T) by MTT test in vitro and imatinib was used as a control drug. Among these compounds, 3a exhibited the best activity against all the leukemic cell lines, except Reh cell line. For Nalm-6, K562, Jurkat, and Molt-4 cell lines, IC50 values were found to be 15.98, 19.12, 23.15, and 25.80 & mu;M, respectively. Our work focuses on the synthesis of original and novel 1,2,3,4-tetrazine derivatives while contributing to the ongoing effort to discover more potent new antileukemia agents. Eleven novel 1,2,3,4-tetrazine derivatives were synthesized via [3 + 3] cycloaddition reaction between in situ formed aza-oxyallyl cations and azides and their anticancer activities were evaluated against five different leukemia cell lines and one non-leukemic cell line. Compound 3a showed the best activity in all cell lines except the Reh cell line. Docking studies showed that DHFR could be a potential target protein for these new compounds and the binding structures of some compounds were investigated.image
Keywords: 1,2,3,4-tetrazine renal fibrosis; anticancer activity; azaoxyallyl cations; leukemia cell line; MTT assay; DIHYDROFOLATE-REDUCTASE; CYCLOADDITION REACTIONS; ANTITUMOR-ACTIVITY; 3+2 ANNULATION; IN-VITRO; ACCESS; DYNAMICS; PHARMACOLOGY; GROMACS; Biochemistry & Molecular Biology; Pharmacology & Pharmacy